Use of Euphorbia Kamerunica (Spurge) Extract in the Control of Saprolegnia Species Growth in Incubated Eggs of Clarias Gariepinus (Global Journal of Science Frontier Research, 2013)
Saprolenia is a major aquatic fungus affecting the smooth successful operation of fish hatcheries because it causes mortality during incubation. A number of cheap synthetic antifungal products have been prohibited because of human health risks associated with them. A study was conducted to investigate the antifungal potential of Euphorbia kamerunica (Spurge) using latex from fresh extract. Fertilized catfish (Clarias gariepinus ) eggs were incubated in three different treatment concentrations of 100ml, 50ml and 25ml extract with a control.This study on the effectiveness of Euphorbia kamerunica (Spurge), a perennial woody shrubs whose caustic milky sap (Latex) is readily soluble in water was extracted as anti fungi agent on the growth of Saprolegnia species on incubated eggs of Clarias gariepinus species.The study revealed that was a significant difference (P
Keywords: spurge; saprolegnia; incubation; fungi extract; concentration